Rise of Violent Non-State Actors in the Middle East : Case Studies of ISIS, Al Qaeda, and Hamas - Benda, Adam; Weinfurter, Jaroslav; Garlick, Jeremy; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the rise of violent non-state actors in the Middle East through case studies of Al Qaeda, the Islamic State in Iraq and Syria, and Hamas. It investigates conditions and common patterns that enabled these groups to reach their respective influence and power peaks, whilst using the theoretical frameworks of functional holes and liminal spaces. The study employs a qualitative, comparative case study approach with Process Tracing methodology to explore how state capacity gaps and contested sovereignty create environments favourable to emergence and expansion of such actors. Findings suggest that despite their differences in ambitions, structure, and scope, these organizations share similarities in how they exploit state weaknesses, fill governance voids, and challenge the Westphalian state model. Understanding these patterns offers insights for anticipating and mitigating future threats posed by similar actors.
Vedoucí práce: Jaroslav Weinfurter
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses